Effect of Ni content on the microstructure, mechanical properties and erosive wear of Mo2NiB2–Ni cermets. Issue 16 (November 2019) - Zhang, Lei; Huang, Zhifu; Liu, Yangzhen; Shen, Yupeng; Li, Kemin; Cao, Zhen; Ren, Zijun; Jian, Yongxin
Abstract: This work revealed the effects of Ni content on the microstructure, mechanical properties and erosive wear of Mo2 NiB2 –Ni cermets. Four groups of Mo2 NiB2 –Ni cermets with different Ni contents were fabricated by reaction boronizing sintering in this study, and their mechanical properties were tested. The results show that the microstructure of the cermets can be obviously refined with the Ni/B increasing from 0.9 to 1.2, and the cermets of Ni/B 1.1 have the best mechanical properties (hardness HRA 90.3 and fracture toughness 24.3 MPa m 1/2 ). Moreover, under high-speed slurry (artificial seawater mixed with SiO2 sand) erosive wear, the cermets of Ni/B 0.9 and 1.0 indicate high wear rate with the aggravated eroded surfaces. However, the cermets of Ni/B 1.1 achieve the minimum wear rate with relatively complete eroded surface, which is attributed to the interaction of Mo2 NiB2 hard phase and Ni binder phase with appropriate ratio of two phases.